HUBUNGAN PELAYANAN POSYANDU LANSIA DENGAN TINGKAT KEPUASAN LANSIA DI WILAYAH KERJA PUSKESMAS RANOMUUT KECAMATAN PAAL II KOTA MANADO (JURNAL KEPERAWATAN, 2018)
Abstract : Integrated posyandu service of elderly is integrated service postal of the public for old age in a specific area which has been agreed, driven by a society where they can get health care. Our satisfaction of the patientis such a level of patient feelings that arise as a result of the performanceof the health care acquired after patient comparing it to what is satisfactory. Satisfaction of the elderly is one sign of the success of the implementation of the programs of integrated service post elderly. The aim of this research is to know the relationship of integrated service postal with the level of satisfaction of the elderly in region of Ranomuut public health center Paal II districts Manado city. Research of design uses descriptive correlation research and cross sectional design. Sample as many as 59 respondents taken using purposive sampling technique. The result collected from respondents using a questionnaire sheet integrated service postal and the level of satisfaction of the elderly. Then presented in the table 2x2 with the help of the computer program using Chi Square test 95% significance level Î± = 0,003. Research Results showed the existence of the relationship of integrated service postal with the level of satisfaction of the elderly in region of Ranomuut public health center Paal II districts Manado city. Keyword : Integrated service postal of elderly, level of satisfaction of the elderly. Abstrak : Posyandu lansia adalah pos pelayanan terpadu untuk masyarakat usia lanjut di suatu wilayah tertentu yang sudah disepakati, yang digerakkan oleh masyarakat dimana mereka bisa mendapatkan pelayanan kesehatan. Kepuasan pasien adalah suatu tingkat perasaan pasien yang timbul sebagai akibat dari kinerja layanan kesehatan yang diperolehnya setelah pasien membandingkannya dengan apa yang diharapkannya. Kepuasan lansia adalah salah satu tanda keberhasilan terlaksananya program-grogram pelayanan posyandu lansia. Tujuan dalam penelitian ini adalah untuk mengetahui hubungan pelayanan posyandu lansia dengan tingkat kepuasan lansi di wilayah kerja Puskesmas Ranomuut Kecamatan Paal II Kota Manado. Desain Penelitian yaitu menggunakan penelitian deskriptif kolerasi dengan rancangan Cross Sectional. Sampel sebanyak 59 responden yang diambil dengan menggunakan teknik Purposive Sampling. Data dikumpulkan dari responden dengan menggunakan lembar kuesioner pelayanan posyandu dan tingkat kepuasan lansia. Kemudian disajikan dalam table 2x2 dengan bantuan program computer menggunakan uji Chi Square pada tingkat kemaknaan 95% Î± = 0,003. Hasil penelitian menunjukan adanya hubungan antara pelayanan posyandu lansia dengan tingkat kepuasan lansia di wilayah kerja Puskesmas Ranomuut Kecamatan Paal II Kota Manado. Kata Kunci: Pelayanan posyandu lansia, tingkat kepuasan lansia.